A low-distortion CMOS analogue voltage follower for high-speed ADCs. (August 2016) - Yang, Yintang; Zhang, Liang; Zhu, Zhangming; Ding, Ruixue
Abstract: This paper presents a low-distortion CMOS analogue voltage follower for high-speed medium-bit analog-to-digital converters (ADCs). The improved circuit is based on a wideband fully differential source-follower configuration. To eliminate the channel length modulation, lower-threshold cascode transistors are adopted. Furthermore, the body effect is removed by quasi-floating bulk (QFB) technique. Therefore, the linearity of the proposed source follower is superior to the conventional ones. The improved circuit has been designed and simulated by SPECTRE with a standard BSIM4 65 nm CMOS technology. It achieves over 68 dB spurious free dynamic range (SFDR) with a 1.2 Vpp 1 GHz differential sinusoid input signal. The circuit consumes 2.6 mW with a 1.8 V power supply.